Revision of the genus Sialis from Oriental China (Megaloptera: Sialidae) - Liu, Xingyue Y.; Yang, Ding (Zootaxa, 2006)
The species of the genus Sialis from Oriental China are revised. The following three species are described as new to science: Sialis elegans sp. nov., Sialis kunmingensis sp. nov., and Sialis versicoloris sp. nov. A key to the species of Sialis from Oriental China is presented.